PERSONALISED LEARNING WITH AI: IMPLICATIONS FOR IGNATIAN PEDAGOGY - Risang Baskara (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2023)
Artificial intelligence (AI) has the potential to transform education by enabling personalized learning experiences, fostering collaboration and communication, and cultivating critical thinking and problem-solving skills. However, ethical issues such as privacy, bias, and the impact of technology on values and beliefs must be considered. This paper explores the implications of integrating AI into education from the perspective of Ignatian pedagogy, a Jesuit-inspired educational approach rooted in certain principles and values. Drawing on a comprehensive review of existing literature on AI in education and Ignatian pedagogy, this paper investigates how AI can support the goals of Ignatian pedagogy while addressing ethical concerns. The paper presents examples of AI use in educational settings, highlighting the potential benefits and ethical challenges. Notably, there is a gap in research on how AI aligns with the values and goals of different educational approaches, including Ignatian pedagogy. To address this gap, this paper examines the potential of AI to support Ignatian pedagogy and identifies critical ethical considerations that should be addressed. Our findings suggest that AI has the potential to support Ignatian pedagogy, but such integration requires thoughtful consideration of ethical issues. Further research is needed to evaluate the potential of AI to support Ignatian pedagogy and other educational approaches while addressing ethical concerns such as privacy, bias, and the impact of technology on values and beliefs.